2015
DOI: 10.1103/physrevlett.115.135501
|View full text |Cite
|
Sign up to set email alerts
|

Low Speed Crack Propagation via Kink Formation and Advance on the Silicon (110) Cleavage Plane

Abstract: We present density functional theory based atomistic calculations predicting that slow fracturing of silicon is possible at any chosen crack propagation speed under suitable temperature and load conditions. We also present experiments demonstrating fracture propagation on the Si(110) cleavage plane in the ∼100 m=s speed range, consistent with our predictions. These results suggest that many other brittle crystals could be broken arbitrarily slowly in controlled experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 32 publications
4
32
0
Order By: Relevance
“…Possible resolutions include: (1) improved interatomic potentials, e.g. coarse-grained from electronic structure in the bond order potential formulation [126] or automatically constructed using machine learning (ML) from a database of reference quantum mechanical (QM) configurations [10,15], (2) concurrent multiscale approaches where localised regions are modelled with QM precision within a non-uniform precision embedding scheme [17] enabling direct simulation of complex crack tip chemistry [97].…”
Section: Atomistic Simulationsmentioning
confidence: 99%
“…Possible resolutions include: (1) improved interatomic potentials, e.g. coarse-grained from electronic structure in the bond order potential formulation [126] or automatically constructed using machine learning (ML) from a database of reference quantum mechanical (QM) configurations [10,15], (2) concurrent multiscale approaches where localised regions are modelled with QM precision within a non-uniform precision embedding scheme [17] enabling direct simulation of complex crack tip chemistry [97].…”
Section: Atomistic Simulationsmentioning
confidence: 99%
“…Figure 4 depicts the stress intensity factor at failure K If versus the specimen width W and the comparison with other works. [20,42] To investigate the behavior of the stress intensity factors at fracture on the continuum side, the values of K If are normalized with respect to the K If obtained for the largest specimen W = 198.41 nm and compared in Figure 5. Since K If is evaluated at fracture, it can be regarded as a good approximation of the fracture toughness, which shows a clear scale independence.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular dynamics simulations explained this threshold as a consequence of a localized phase transformation in the vicinity of the crack tip [13] that delays the fracture initiation. However, a recent work suggested that the velocity gap should not be considered as an universal indication, since an extremely low speed (in 100 m/s speed range) cleavage along (110) can stably take place via kink formation and advance under a suitable temperature and some specific loading conditions [14]. This new finding reveals that the external conditions need to be carefully considered when investigating the fracture in silicon.…”
mentioning
confidence: 97%